Regeneration of the Anterior Talofibular Ligament Following PRP Therapy: A Case Report with Serial MRI Evidence - See, Zhi Huang; Low, Sing Wei; Tan, Seu Kean (Heca Sentra Analitika, 2025)
Lateral ankle sprain (LAS) is one of the most common lower limb injuries, particularly in individuals involved in sports and recreational activities. The anterior talofibular ligament (ATFL) is the structure most frequently affected. Platelet-rich plasma (PRP) has shown potential in promoting tissue regeneration and accelerating healing. We report a case of a grade 3 ATFL tear treated with a single PRP injection combined with functional rehabilitation therapy, with serial MRI scans demonstrating ligament continuity and clinical recovery. This case highlights PRP hypothesized as a useful adjunct treatment for LAS involving ATFL injury when combined with functional rehabilitation, as it may promote ligamentous healing, improve short-term symptoms, and potentially reduce the long-term risk of developing chronic ankle instability.